2016
DOI: 10.5455/msm.2016.28.324-328
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Ribotyping and Antimicrobial Resistance Properties of Clostridium difficile Strains Isolated From The Cases of Diarrhea

Abstract: Background:Clostridium difficile is the most prevalent cause of antibiotic-associated infectious diarrhea al-around the world. Prevalence of virulent and resistant strains of Clostridium difficile is increasing now a day. The present investigation was carried out to study the prevalence, ribotyping and antibiotic resistance pattern of C. difficile isolated from diarrheic and non-diarrheic pediatrics.Materials and methods:Four-hundred stool specimens were collected from the diarrheic and non-diarrheic pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
10
1
2
Order By: Relevance
“…In Iran, few studies were performed on the PCR-ribotyping of CDI, and it is not possible to compare our results with previously published data due to incoherence or the absence of molecular typing methods (6). A recent study conducted on 400 pediatric stool specimens in Iran reported a high prevalence for R27 (14.28%), R1 (10.71%), R12 (7.14%), R13 (7.14%), and R18 (7.14%) (21). In another study in Iran, Khoshdel et al (2015) (22) reported that the most commonly detected RTs in the C. difficile isolates of pediatrics were RT027 (11.52%), RT01 (9.61%), and RT013 (7.68%).…”
Section: Discussioncontrasting
confidence: 59%
“…In Iran, few studies were performed on the PCR-ribotyping of CDI, and it is not possible to compare our results with previously published data due to incoherence or the absence of molecular typing methods (6). A recent study conducted on 400 pediatric stool specimens in Iran reported a high prevalence for R27 (14.28%), R1 (10.71%), R12 (7.14%), R13 (7.14%), and R18 (7.14%) (21). In another study in Iran, Khoshdel et al (2015) (22) reported that the most commonly detected RTs in the C. difficile isolates of pediatrics were RT027 (11.52%), RT01 (9.61%), and RT013 (7.68%).…”
Section: Discussioncontrasting
confidence: 59%
“…Increasing age >65 is another known risk factor associated with CDI, accounting for the majority of diarrheal cases in residential facilities 2226. In the United States alone, near half a million cases have been reported with 29,000 fatalities attributed to CDI 27.…”
Section: Introductionmentioning
confidence: 99%
“…The articles which fulfill eligibility criteria for this systematic review and meta-analysis were conducted. Seven studies from Iran [12,[38][39][40][41][42][43]; two studies in China [44,45]; one study in the United States [46]; one study in European Union (EU) [47]; one study in Poland [48]; one study in Scotland [49]; one study in South Korea [50] and lastly one study in Thailand [51]. All of these studies were done by cross-sectional study design and conducted among hospitalized diarrheal patients (Table 1).…”
Section: Selection and Characteristics Of Included Studiesmentioning
confidence: 99%